O14 Investigating the recent infection testing algorithm (RITA): predictors of recent HIV infection among GUM clinic attendees. (23rd May 2012) - Rayment, M; Aghaizu, A; Toswill, J; Murphy, G; Hughes, G; Delpech, V
Abstract : Background: Testing for recent infection with HIV has been part of routine national surveillance in the UK since 2009. These data can be used to estimate HIV seroincidence in populations. For these estimates to be accurate, HIV testing behaviour must be independent of HIV acquisition risk. This is unlikely to be true, as much testing may be motivated or clinically indicated. Aims: To identify demographic and behavioural differences between individuals diagnosed with recent (<6 months) vs longstanding HIV infection, and to assess the possible level of bias introduced by motivated testing. Methods: Recent Infection Testing Algorithm (RITA) results were linked to Genitourinary Medicine Clinic Activity Dataset attendance records (providing data on attendance and sexual health) for the year preceding the date of RITA test and/or HIV diagnosis. Univariate analyses were performed examining age, sexual orientation, GUM clinic attendances, and STI history, to identify predictors of being diagnosed at early stages of HIV infection. Results: Preliminary analyses show that among 628 newly diagnosed HIV-positive individuals, 14% (85/628) were diagnosed with recent HIV infection. Being diagnosed with a recent HIV infection was positively associated with younger age, men who have sex with men and having been diagnosed with any bacterial STI in the year preceding the HIV diagnosis (see Abstract O14 table 1 ). Those visiting a sexual health clinic more than twice in the previous year were also more likely to be diagnosed at early stages of HIV infection. Conclusions: Important behavioural and demographic differences exist between individuals diagnosed with recent vs established HIV infections. Such differences must be considered when deriving incidence estimates among key at-risk groups. Further work to examine these trends among all RITA results, in particular the relationship with HIV testing patterns, is ongoing.